The role of the audio-braille library in contributing towards academic performance of visually impaired students at the University of Limpopo - Phukubje, Kolobe Justice (University of Limpopo, 2019)
The contribution of library and information services in general towards academic performance improvement of visually impaired students cannot be emphasised. At the University of Limpopo, visually impaired students, like any other students, are continually exposed to an overwhelming mass of visual materials such as textbooks, course outlines, class timetables, lecture notes, whiteboards, writing, memos etcetera. In addition, the use of videos, computers and Blackboard adds to the volume of visual materials to which they have only limited access. One would content that the University of Limpopo, especially after establishing the Audio-Braille library, has done reasonably well in a bid to improving library services of students living with disabilities, however, this is not the reality to the visually impaired themselves. The purpose of the study was to evaluate the role of the Audio-Braille library in contributing towards the academic performance of students with visual impairments at the University of Limpopo, South Africa. Both quantitative and qualitative methods were employed in this study. The researcher distributed questionnaires to all visually impaired students registered for the 2017 academic year at the University of Limpopo’s Reakgona Disability Centre and conducted interviews with the lecturers who teach these students. The findings indicate that although many students acknowledged the library’s contribution, a greater number of respondents revealed that the library lack relevant up-to-date academic reading material in alternative formats such as braille, large print as well as electronic. The main value of this study is to impart knowledge by pointing out major contributions of the Audio-Braille library with hope that this knowledge will encourage and motivates visually impaired students to make use of the library. Students could improve on their academic performance, abilities and possibilities, and boost their confidence and self-esteem by fully using the Audio-Braille library and its resources. Access to the relevant library facilities and resources ameliorates effects of their disabilities and gives them a chance to be “equal” to the so-called normal students v The findings of this study will also help in enhancing both the quality of education for the visually impaired, as well as the Audio-Braille library services because there is still a lot of inexperience around library services for visually impaired students at the University of Limpopo and maybe in other universities as well. Therefore, the AudioBraille library must ensure that all visually impaired students receive unsurpassed library and information services like any other students by expanding its collection so that student receive books, information, lecturer notes and other study materials that they need in their academic development process in appropriate formats.
Thesis (M. A. (Information Studies)) -- University of Limpopo, 2019
Keywords: Library and information services; Academic libraries; Visually impaired students; Academic performance; Academic libraries -- Services to people with disabilities -- South Africa -- Limpopo; Libraries and people with visual disabilities; Students with disabilities Services for -- South Africa -- Limpopo; People with visual disabilities; Academic achievement